ANALISIS FAKTOR – FAKTOR PENYEBAB ANAK PUTUS SEKOLAH TINGKAT SMA DI DESA SIMODONG KECAMATAN SEI – SUKA KABUPATEN BATU – BARA - Elisabeth Manurung; Fauzi Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to identify the factors causing senior high school students to drop out in Simodong Village, Sei Suka District, Batu Bara Regency. The study employed a quantitative approach with a descriptive method. The sample consisted of 19 school dropouts selected using the total sampling technique. Data were collected through an open-ended questionnaire and analyzed using descriptive percentage analysis. The results showed that the causes of school dropout consisted of external and internal factors. The most dominant external factors were parents' socioeconomic condition and parents' perception of education, each accounting for 42.11%, while the dominant internal factor was students' low learning interest at 36.84%. It can be concluded that external factors have a greater influence on school dropout than internal factors.